ANALISIS VALIDITAS DAN RELIABILITAS PADA PENELITIAN PENGELOLAAN KELAS TERHADAP MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMK TELKOM PEKANBARU - Ririn Ristiani; Risnawati; Miftahir Rizqa; M. Fikri Hamdani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the validity and reliability of the questionnaire instrument used to measure classroom management variables and student learning motivation in Islamic Religious Education (PAI) at SMK Telkom Pekanbaru. The classroom management instrument consists of 23 statements, while the learning motivation instrument consists of 20 statements, each arranged using a Likert scale. This study uses a quantitative approach with a correlational method, involving 24 respondents selected by random sampling. The validity test was conducted using Pearson Product Moment correlation, while the reliability test was analyzed using Cronbach's Alpha through SPSS. The results showed that all statement items in both instruments had a calculated r value greater than the r table (0.273), so all items were declared valid. The reliability test showed that the classroom management instrument had a Cronbach's Alpha value of 0.836 and the learning motivation instrument of 0.910, both of which were above the minimum limit of 0.70. Thus, both instruments were reliable and suitable for use in research. These findings confirm that the questionnaire instrument has met the psychometric feasibility standards for measuring classroom management and student learning motivation accurately, and can be a reference for research and Islamic Education teaching practices in increasing the effectiveness of classroom management and student learning motivation.